PENGARUH AKUNTABILITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (LKPD) TERHADAP TINGKAT KORUPSI PEMERINTAH DAERAH (STUDI KASUS SKPD KEPUALAUAN RIAU) - Aznedra Aznedra; Nurhayaty Nurhayaty; Rizki Eka Putra (Universitas Riau Kepulauan, 2020)
This research was conducted at the Riau Islands SKPD with the aim to find out and analyze the Effect of the Accountability of the Regional Financial Statements (LKPD) Against Regional Government Corruption (Case Study of the Riau Islands SKPD). This research uses descriptive analysis and statistical analysis methods. The results of the analysis of audit opinion with a proxy for four types of audit opinions issued by the Indonesian Audit Board of the Republic of Indonesia on the financial statements of the local government on the corruption perception index showed that the audit opinion variable (X1) t value was 2,272 with a probability of 0.211. With t count 2,272 greater than t-table 0.05 (40) 2,021 or probability 0.211 greater than 0.05; then H0 is accepted which means that the Audit Opinion variable (X1) partially or individually has no significant effect on the Corruption Perception Index (Y) in the Riau Islands Province LKPD. This result means that the audit opinion issued by BPK RI does not affect the perception of the regional government. Although the results of an opinion from a fair LKPD without exception does not mean that the government has a low level of corruption